The impact of the ketogenic diet on the course of schizophrenia and bipolar disorder - Klimczak, Klaudia; Protasiuk, Agnieszka; Żak-Gontarz, Agata; Sierzpowski, Rafał; Tymoszuk, Patrycja; Kasperek, Bartosz; Augustowska, Katarzyna; Budzyńska, Kamila; Loryś, Laura (Quality in Sport, 2025)
Introduction and purpose Schizophrenia (SZ) and bipolar disorder (BPD) are serious mental disorders that significantly affect the functioning and efficiency of a person. The ketogenic diet (KD) reduces inflammation in the body and improves the efficiency of the nervous system. The aim of this article is to present the impact of the ketogenic diet on the course of these diseases. Material and methods The review was conducted based on the analysis of materials collected in the "PubMed" databases. The following keywords were entered when searching for scientific articles: ketogenic diet; bipolar affective disorder; schizophrenia; pathophysiology of schizophrenia; ketogenic diet shizophrenia; ketogenic diet bipolar disease. A total of 32 articles published in 2020-2025 were taken into account for the study and their relevance in the context of the topic of the effect of the ketogenic diet on the course of schizophrenia and bipolar disorder was verified. Description The way of eating significantly affects the human body. It provides it with fuel for functioning and soothes the symptoms of many diseases. It is worth focusing on the KD, which has been proven to have a wide range of effects: from anti-inflammatory, through mood stabilization and reduction of productive symptoms, to weight loss and improvement of laboratory test parameters. Summary Bipolar disorder and schizophrenia are psychiatric conditions that significantly impair a person’s life and functioning. Their treatment most often involves pharmacotherapy, which may be ineffective in controlling symptoms. In such cases, a ketogenic diet can be used to help stabilize mood and alleviate symptoms of a psychological nature. Therefore, expanding research in this direction may be crucial in developing new strategies to support the treatment of BPD and SZ with KD.